2013
DOI: 10.1094/pdis-01-13-0016-re
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity, Virulence, and Vegetative Compatibility Grouping of Verticillium Isolates from Spinach Seed

Abstract: Iglesias-Garcia, A. M., Villarroel-Zeballos, M. I., Feng, C, du Toit, L. J., and Correll, J. C. 2013. Pathogenicity, virulence, and vegetative compatibility grouping of Verticillium isolates from spinach seed. Plant Dis. 97:1457-1469.In 2005, Verticillium dahliae was first reported to be pathogenic to spinach seed crops in the Pacific Northwest, with symptoms only developing after initiation of the reproductive stage of plant growth, and to be prevalent on commercial spinach seed lots produced in Denmark, The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 71 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…Endophytism seems to be a common phenomenon in the genus Verticillium, although often overlooked (Lacy and Horner 1966;Malcolm et al 2013). It has been demonstrated that certain isolates of V. dahliae, V. alboatrum and V. tricorpus can colonize their hosts and yet cause no or minor vascular discolouration and do not develop external symptoms (Skotland 1971;Ebihara et al 2003;Chen et al 2004;Robinson et al 2006;Qin et al 2008;Iglesias-Garcia et al 2013;Malcolm et al 2013). However, it is still unclear whether the endophytic behaviour is generally an intrinsic characteristic of certain isolates or rather the outcome of specific interactions between potential pathogenic isolates and some hosts (Malcolm et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Endophytism seems to be a common phenomenon in the genus Verticillium, although often overlooked (Lacy and Horner 1966;Malcolm et al 2013). It has been demonstrated that certain isolates of V. dahliae, V. alboatrum and V. tricorpus can colonize their hosts and yet cause no or minor vascular discolouration and do not develop external symptoms (Skotland 1971;Ebihara et al 2003;Chen et al 2004;Robinson et al 2006;Qin et al 2008;Iglesias-Garcia et al 2013;Malcolm et al 2013). However, it is still unclear whether the endophytic behaviour is generally an intrinsic characteristic of certain isolates or rather the outcome of specific interactions between potential pathogenic isolates and some hosts (Malcolm et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, significant differences in morphology and physiology have been reported between different VCGs (Korolev et al 2000;Zeise and von Tiedemann 2001;Papaioannou et al 2013b). The phytopathological significance of VCG analyses for V. dahliae populations is reflected in the unabated frequency of relevant reports in the literature (some recent examples include Dung et al 2013;El-Bebany et al 2013;Iglesias-Garcia et al 2013;Papaioannou et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…cicla ), Peronospora variabilis (cause of downy mildew on quinoa, Chenopodium quinoa ), Verticillium tricorpus and Verticillium nigrescens (saprophytes or weak pathogens of spinach often found associated with spinach seed) (Iglesias‐Garcia et al . ), V. albo‐atrum (from alfalfa, Medicago sativa ), V. fungicola (from mushroom), Colletotrichum dematium (cause of spinach anthracnose), Fusarium oxysporum f. sp. spinaciae (cause of Fusarium wilt of spinach), and multiple saprophytic fungal isolates including F. oxysporum , Alternaria spp., Phoma spp., Epicoccum spp.…”
Section: Methodsmentioning
confidence: 99%
“…; Iglesias‐Garcia et al . ). Additionally, Cladosporium leaf spot, caused by Cladosporium variabile , and Stemphylium leaf spot, caused by Stemphylium botryosum , have recently emerged as problems for spinach production as well as spinach seed production (Fuentes‐Davila and Gabrielson ; Everts and Armentrout ; Koike et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation